Expanding Religious Freedom Through Organizational Forms: Kebatinan, Sufism and The Global Growth Movement in Indonesia’s Spiritual Training Industry - Muttaqin, Ahmad; Sulistiyanto, Priyambudi (Al-Jami'ah Research Centre, 2024)
In Indonesia, the practice of religious freedom remains deeply contested, with marginal spiritual movements often subject to stricter limitations than their officially recognized counterparts. This paper investigates two hybrid spiritual groups in contemporary Indonesia, Bhakti Nusantara and Bionergi, based in Yogyakarta, which integrate elements of Javanese spiritual traditions (Kebatinan), Sufism, and facets of the Global Growth Movement. Despite their syncretic practices, these organizations occupy a distinctive social position that grants them greater latitude in religious and spiritual expression. By comparing them with other fringe spiritual movements that have faced criticism and blasphemy charges, this paper argues that their status as spiritual or religious corporations enables them to enjoy broader freedoms. This distinction highlights the complexities of religious freedom and its dynamic governance in Indonesia, where the legal and social treatment of spiritual groups can vary significantly depending on their organizational shape and social location.[Di Indonesia, praktik kebebasan beragama tetap menjadi isu yang masih sering diperdebatkan dan gerakan spiritual marginal sering kali mendapat tantangan yang lebih berat dibandingkan kelompok keagamaan resmi. Makalah ini mengkaji dua kelompok spiritual hibrida di Indonesia kontemporer, Bhakti Nusantara dan Bionergi, yang berbasis di Yogyakarta, yang mengintegrasikan elemen tradisi spiritual Jawa (Kebatinan), Tasawuf, dan elemen-elemen dari Global Growth Movement. Meskipun bersifat sinkretik, dua kelompok ini mempunyai posisi sosial unik. Konfigurasi organisasi yang unik memberi mereka kebebasan yang lebih luas dalam mengekspresikan praktik keagamaan dan spiritual. Dibandingkan dengan gerakan-gerakan spiritual pinggiran lain yang sering mendapat kritik dan tuduhan penodaan agama, dua kelompok ini dengan status sebagai korporasi spiritual mendapat kebebasan yang lebih luas. Temuan ini menandakan kompleksitas dan dinamika tata kelola kebebasan beragama di Indonesia, bahwa ragam perlakukan kebebasan yang didapat secara sosial dan legal suatu kelompok spiritual turut ditentukan oleh bentuk organisasi dan lokasi sosialnya.]